(untitled) (Spectrum, 2022)
Peter Shaffer in his play Equus, portrays Dora Strang, a mother who allegedly provokes her son Alan to commit the crime of blinding six horses. Critics have labelled her the prime agent culpable for Alan’s misdeed. However, a proper analysis and investigation of the playtext reveals Dora as a victim of social pressures. The socio-economic environment of Shaffer’s Post-war British society relied heavily on Sigmund Freud and his theories on family relationships. The mother-blaming tradition flourished in literature when authors and literary experts misinterpreted Freud’s ideologies and employed them to degrade the mother’s maternal commitments and efforts. They held her responsible for her child’s misconducts. Early critics contended that Peter Shaffer was also following this tradition. However, this paper will show that he somewhat differs from it. Dora was frustrated because she adopted ‘motherhood’ as a full-time job like the majority of British middle class women, according to the contemporary social demands. She invested all her skills and energy in child care by discarding her intellectual and professional growth. Consequently, she became disappointed, and she infused her frustrations in Alan. This eventually showcased delinquency in him. In addition, her husband Frank is equally responsible for their son’s misconduct. In light of Freudian psychoanalysis, this paper studies how Dora’s frustration with her limited life provokes Alan’s misdemeanors. Also, by analyzing Freud’s concept of the Father, it shows how Frank as a father drives Dora towards frustration and Alan towards delinquency. Spectrum, Volume 16, June 2021: 159-172